Portofolio Saham Optimal dengan Mean-Gini dan Modigliani-Squared: Studi Kasus Saham JII - Akbar, Akbar; Ekawati, Darma (Journal of Mathematics: Theory and Applications, 2025)
This study aims to develop the composition and determine the optimal portfolio of stocks listed in the Jakarta Islamic Index (JII) 70 using a quantitative approach. The Mean-Gini method is employed to obtain the portfolio with the highest expected return and the lowest risk. The data analyzed consists of monthly closing prices of five JII 70 stocks, namely TLKM (Telkom Indonesia), ISAT (Indosat), ADRO (Adaro Energy Indonesia), BRMS (Bumi Resources Minerals), and CTRA (Ciputra Development), covering the period from January 2020 to December 2023. The performance of the optimal portfolio is evaluated using the Modigliani–Squared (M²) method on 25 portfolio combinations. The results indicate that the optimal portfolio, based on the M² index, is the first portfolio, comprising two stocks with an investment proportion of 34.32% in BRMS and 65.68% in ADRO. These findings provide strategic insights for constructing an efficient Sharia-compliant portfolio based on risk and return considerations.